The Effects of Landmine and UXO Accidents on Survivor\'s Quality of life in 5 western provinces of Iran - F. falahati; M.R. Soroush; H. Haghani; Sh. khateri (Afarand Scholarly Publishing Institute, 2009)
Background : Today, the burden of landmines and explosive remnants of wars is a global concern. Affected populations' quality of life is invariably affected by the impact of mine associated incidents which are characterized by sudden onset and long term (probably lifelong) complications.   Lack of comprehensive information, made us take on this study to evaluate the quality of life indices among landmine victims, un-injured dwellers of same areas and normal populations of same age, gender and socio economic variables who live outside mine infested territories   Method and Material: In this case control study, some quality of life indices were compared between 348 victims of landmines and other left over explosives who were included in the study by simple accidental sampling from victims' register in each of the 5 Iranian mine infested provinces and people of same age and gender who live in same areas and those who live outside the infested areas. Data collection tools included demographic questionnaires and SF_36   Results : The results of the study showed that the quality of life in all respects as evaluated by the SF_36, is significantly lower among mine   Discussion :The impacts of living in the presence of war explosive remnants is significant enough to mandate special measures like periodic health checkups, screening programmes and establishment of mental and physical rehabilitation centers for the affected populations in Iran.